THE EFFECT OF SELF REGULATED LEARNING AND SELF EFFICACY ON STUDENTS’ LEARNING OUTCOMES IN ARCHIVE SUBJECT AT SMK NEGERI 10 SURABAYA - Lailatul Fitriyah; Durinda Puspasari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The study aimed to analyze : 1) the effect of self-regulated learning on students’ learning outcomes in archive subjects at SMK Negeri 10 Surabaya; 2) the effect of self-efficacy on students’ learning outcomes in archive subjects at SMK Negeri 10 Surabaya; 3) the effect of self-regulated learning and self-efficacy on student’ learning outcomes in archive subjects at SMK Negeri 10 Surabaya. This type of this study was a quantitative research. Data were collected through questionnaires and interviews. The population were all students at class X OTKP for as many as 108. The samples of this study were 85 students which were selected proportional random sampling. The instrument of this study was validity test and reliability test. Then, the data were analyzed through: 1) classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test; 2) hypothesis testing using multiple linear regression. The results showed that: 1) there was a significant effect of self-regulated learning on student’ learning outcomes in archive subject at SMK Negeri 10 Surabaya; 2) there was a significant effect of self-efficacy on student’ learning outcomes in archive subject at SMK Negeri 10 Surabaya; 3) there was a significant effect of self-regulated learning and self-efficacy on students’ learning outcomes in archive subject at SMK Negeri 10 Surabaya.